COL8A1 Promotes NSCLC Progression Through IFIT1/IFIT3-Mediated EGFR Activation - Zan, Xiangyi; Li, Shuyan; Wei, Shixiong; Gao, Liping; Zhao, Lanting; Yan, Xiaoxia; Zhao, Yan; Shi, Junnian; Wang, Yuping; Liu, Rong; Zhang, Yuanyi; Wan, Yixin; et al. (Frontiers in Oncology, 2022)
Activation of EGFR is a major risk factor for non-small cell lung cancer (NSCLC). Understanding the molecular events promoting EGFR activation can help us gain more insights into the progression of NSCLC. In this study, we demonstrate that collagen type VIII alpha 1 chain (COL8A1), an extracellular matrix component, was overexpressed in NSCLC. In NSCLC cells, knockdown of COL8A1 suppressed cell growth, cycle progression, and migration, and induced cell apoptosis. While COL8A1 overexpression promoted cell proliferation and inhibited cell apoptosis. In addition, we found that COL8A1 depletion reduced interferon response signaling and downregulated interferon-induced proteins with tetratricopeptide repeats (IFIT1) and interferon-induced proteins with tetratricopeptide repeats 3 (IFIT3). Moreover, we indicated that COL8A1 could upregulate IFIT1 and IFIT3 mediated EGFR activation in vitro and in vivo. Lastly, there was a positive correlation among COL8A1, IFIT1, and IFIT3 expression, and EGFR activity in patients with NSCLC. Overall, our data demonstrate that COL8A1 contributes to NSCLC proliferation and invasion through EGFR activation, dependent on IFIT1 and IFIT3 expression.